2014
DOI: 10.1128/aac.00053-14
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary Posaconazole Penetration at the Infection Site in an Immunosuppressed Murine Model of Invasive Pulmonary Aspergillosis Receiving Oral Prophylactic Regimens

Abstract: c Adequate penetration to the infection/colonization site is crucial to attain optimal efficacy of posaconazole against Aspergillus fumigatus diseases. We evaluated posaconazole exposure in pulmonary epithelial lining fluid (ELF) in a murine model of invasive pulmonary aspergillosis. The posaconazole exposure (area under the plasma concentration-time curve from time zero to 24 h postinfusion [AUC 0 -24 ]) in ELF was 20% to 31% of that in plasma for total drug after the third dose, and the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…in murine models (14,15,22,28,29,36) and the fact that multiple dosing of VRC at 20 mg/kg in mice resulted in an AUC 0 -24 of 58.1 h · mg/liter, leading to efficacy against invasive aspergillosis by a strain with a MIC of 0.25 g/ml (14). Other studies testing PSC and VRC doses similar to those used in our experiment have shown AUC values indicative of correct exposure (28,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 73%
“…in murine models (14,15,22,28,29,36) and the fact that multiple dosing of VRC at 20 mg/kg in mice resulted in an AUC 0 -24 of 58.1 h · mg/liter, leading to efficacy against invasive aspergillosis by a strain with a MIC of 0.25 g/ml (14). Other studies testing PSC and VRC doses similar to those used in our experiment have shown AUC values indicative of correct exposure (28,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 73%
“…Plasma was aspirated, transferred in two 2-ml plastic tubes, and stored at Ϫ80°C. BAL fluid samples were obtained using a technique described previously (37). After being sacrificed under isoflurane anesthesia followed by cervical dislocation, the mice were secured on a plastic platform.…”
mentioning
confidence: 99%
“…The concentration of isavuconazole in epithelial lining fluid (ELF) was then determined by using the ratio of urea concentration in BAL fluid to that in plasma. The drug concentration in ELF was then estimated, as described previously (37,(39)(40)(41)(42)(43)(44): drug concentration ELF ϭ drug concentration BAL fluid ϫ urea plasma /urea BAL fluid .…”
mentioning
confidence: 99%
“…Blood was sampled by retro-orbital puncture into heparin-containing tubes, and plasma was separated by centrifugation at 3,000 ϫ g for 10 min at 4°C. BAL fluid was obtained using a previously reported technique (17,25). In short, mice were humanely sacrificed under isoflurane anesthesia, followed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%